2023
DOI: 10.1186/s12912-023-01474-8
|View full text |Cite
|
Sign up to set email alerts
|

Nursing workforce competencies and job satisfaction: the role of technology integration, self-efficacy, social support, and prior experience

Mohammed Hamdan Alshammari,
Atallah Alenezi

Abstract: Background The nursing profession has significant importance in delivering high-quality healthcare services. Nursing practitioners who have essential competencies and who are satisfied with their job are vital in achieving optimum patient outcomes. Understanding the effects of technology integration on nurse workforce competencies and job satisfaction is crucial due to the fast progress of technology in healthcare settings. Furthermore, many elements, including self-efficacy, social support, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…From the results in Table 10 showing the relationship between the IT competencies and job satisfaction, the statistical analysis of the data indicates that there is an overall significant relationship between technical competencies and job satisfaction (r = 0.278, p = 0.0117), managerial competencies and job satisfaction (r = 0.2616, p = 0.0431), and socio-interpersonal competencies and job satisfaction (r = 0.308, p = 0.0057). Based on this general assessment that there exists a substantial relationship between job satisfaction and several key factors, including economic security, professional growth opportunities, socio-cultural adaptability, and IT competencies in various dimensions, this aligns with the earlier mentioned studies of Kucharska and Erickson (2019), as well as the study of Alshammari and Alenezi (2023). The significant positive correlation between technical competency and economic security (r = 0.2425, p = 0.01406) means that Filipino IT workers who possess higher technical competency levels are more likely to have better economic security.…”
Section: 03 Much Satisfiedsupporting
confidence: 78%
See 1 more Smart Citation
“…From the results in Table 10 showing the relationship between the IT competencies and job satisfaction, the statistical analysis of the data indicates that there is an overall significant relationship between technical competencies and job satisfaction (r = 0.278, p = 0.0117), managerial competencies and job satisfaction (r = 0.2616, p = 0.0431), and socio-interpersonal competencies and job satisfaction (r = 0.308, p = 0.0057). Based on this general assessment that there exists a substantial relationship between job satisfaction and several key factors, including economic security, professional growth opportunities, socio-cultural adaptability, and IT competencies in various dimensions, this aligns with the earlier mentioned studies of Kucharska and Erickson (2019), as well as the study of Alshammari and Alenezi (2023). The significant positive correlation between technical competency and economic security (r = 0.2425, p = 0.01406) means that Filipino IT workers who possess higher technical competency levels are more likely to have better economic security.…”
Section: 03 Much Satisfiedsupporting
confidence: 78%
“…Having the skills and knowledge to perform tasks efficiently not only boosts self-assurance but also enables professionals to handle challenges effectively, leading to a greater sense of job satisfaction and fulfillment. This confidence in their abilities often translates into a positive work experience, fostering a fulfilling and contented professional life within the IT sector (Alshammari & Alenezi, 2023).…”
Section: Literature Review Technical Competencymentioning
confidence: 99%
“…Previous ICD coding experience is defined as prior use of ICD 44 , 45 . Past experiences play a significant role in determining intention towards a behaviour like using an innovation 46 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior studies [ 6 12 ] have indicated that social support directly impacts psychological distress, depressive symptoms, life satisfaction, hope, self-transcendence, mortality risk, and so on. Furthermore, social support has been found to mediate relationships between loneliness and depression [ 13 ], mindfulness and mood [ 14 ], stress exposure and psychological distress [ 15 ], chronic diseases and positive mental health [ 16 ], competencies and job satisfaction [ 17 ], and so forth. Thus, sick or not, assessing social support is a key component in many health-related questionnaire surveys.…”
Section: Introductionmentioning
confidence: 99%